2003
DOI: 10.1002/dmrr.372
|View full text |Cite
|
Sign up to set email alerts
|

Nerve collagens from diabetic and nondiabetic Sprague–Dawley and biobreeding rats: an atomic force microscopy study

Abstract: The best means we have found to reduce raw AFM data is to measure several diameters with a single scan, using valley-to-valley measurements. Structural, fibrillar collagens of the nerve and tendon become larger in rats exposed to prolonged diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 46 publications
2
20
0
2
Order By: Relevance
“…Increases in collagen in the endoneurium and perineurium have been identified in human lower extremity nerves in people with Type 1 and Type 2 diabetes (Bradley et al, 2000, Hill, 2009). Increased collagen quantity and fibril diameter have also been identified in the epineurium of the sciatic nerve in rat models of experimentally induced diabetes (Wang et al, 2003, Layton et al, 2004). Greater cross sectional area of the TibN has been demonstrated in people with Type 1 and Type 2 diabetes (Watanabe et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Increases in collagen in the endoneurium and perineurium have been identified in human lower extremity nerves in people with Type 1 and Type 2 diabetes (Bradley et al, 2000, Hill, 2009). Increased collagen quantity and fibril diameter have also been identified in the epineurium of the sciatic nerve in rat models of experimentally induced diabetes (Wang et al, 2003, Layton et al, 2004). Greater cross sectional area of the TibN has been demonstrated in people with Type 1 and Type 2 diabetes (Watanabe et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Because PGA fibers are only 13 μm in diameter, whereas the long axis of an SMC can be >50 μm, it is likely that adherent SMC extended along the long axis of the PGA fibers. Several investigators have shown that collagen-producing cells secrete collagen along their long axes (29,30); hence cellular alignment along PGA fibers may have "forced" the direction of collagen fiber deposition, at least at early times during culture before the PGA fibers degraded. Only after the scaffold fibers degraded did SMC presumably reorient consistent with macroscopic stress or strain fields and then deposit collagen fibers along directions dictated by applied loads.…”
Section: Discussionmentioning
confidence: 99%
“…In an in vivo rat model, larger-than-normal, nonspecific (Type I/Type III) collagen fibril diameters were measured in diabetic rat endoneurium via transmission electron microscopy (TEM) [35]. This was also found in vivo in diabetic humans with TEM [36], and both in vivo and in vitro with rat tail tendon with atomic force microscopy (AFM) [3] and finally, in vitro in endoneurium and epineurium in two diabetic rat models with AFM [17].…”
Section: Measurements In Diabetic Tissues: Prior Artmentioning
confidence: 98%
“…This tissue undergoes glycation [17,18], and exhibits altered mechanical properties, which can be modeled using micromechanics [18,19]. The gross mechanical properties of peripheral nerve [20,21] and collagen fibrils [22,23] have been quantified, but until our own work, there was apparently no model correlating glycation with mechanical properties at the tissue scale.…”
Section: Introductionmentioning
confidence: 99%